Crafting the Eighteenth-Century Singer Introduction - Aspden, S (Cambridge University Press, 2015)
This issue’s focus on the singer in the eighteenth century may, then, seem a little behind the times. But, thanks in large part to the energy with which advocacy for the power of the nineteenth-century singer and her voice has been pursued, and the richness and persuasiveness of such readings, we can now shift our attention to other, perhaps less glamorous, but no less significant areas of interest.